IMPROVING MATERNAL AND FETAL PREGNANCY OUTCOMES BY PREVENTING POSTPARTUM HAEMORRHAGE AND MOTHER TO CHILD TRANSMISSION OF HIV IN PREGNANCY - Frederick Lifangi-Ikomi, Morfaw (My University, 2019)
Background and Objectives: Postpartum haemorrhage (PPH) and mother to child transmission (MTCT) of the Human Immune Deficiency Virus (HIV) are major threats to maternal and foetal health, especially in low and middle income countries. This thesis addressed two main objectives: 1) to investigate strategies for the prevention of PPH, with a focus on misoprostol; 2) to investigate strategies for prevention of mother to child transmission (PMTCT) of HIV, with a focus on the male partner. Methods: We employed a number of study designs including a cross sectional design, a retrospective chart review, and a systematic review which included Classical and Bayesian approaches of meta- analysis. Key methodological issues addressed include the use of propensity score matching methods to address channeling bias; comparison and combination of evidence from different sources; sensitivity analysis in health research; and methods for developing new tools for measurement in health research. Results and Conclusions: Our findings suggests that an oxytocin-misoprostol combination is better than the current standard of care of oxytocin-only which is recommended by the World Health Organisation for the prevention of PPH. Secondly, effectiveness data from well-designed observational studies may be used to inform clinical decisions on misoprostol in the prevention of PPH. Thirdly, using a new tool we have created, it is possible to objectively identify HIV positive women who lack the support of their male partners in adhering to PMTCT recommendations.
Background and Objectives: Postpartum haemorrhage (PPH) and mother to child transmission (MTCT) of the Human Immune Deficiency Virus (HIV) are major threats to maternal and foetal health, especially in low and middle income countries. This thesis addressed two main objectives: 1) to investigate strategies for the prevention of PPH, with a focus on misoprostol; 2) to investigate strategies for prevention of mother to child transmission (PMTCT) of HIV, with a focus on the male partner. Methods: We employed a number of study designs including a cross sectional design, a retrospective chart review, and a systematic review which included Classical and Bayesian approaches of meta- analysis. Key methodological issues addressed include the use of propensity score matching methods to address channeling bias; comparison and combination of evidence from different sources; sensitivity analysis in health research; and methods for developing new tools for measurement in health research. Results and Conclusions: Our findings suggests that an oxytocin-misoprostol combination is better than the current standard of care of oxytocin-only which is recommended by the World Health Organisation for the prevention of PPH. Secondly, effectiveness data from well-designed observational studies may be used to inform clinical decisions on misoprostol in the prevention of PPH. Thirdly, using a new tool we have created, it is possible to objectively identify HIV positive women who lack the support of their male partners in adhering to PMTCT recommendations.
Keywords: Prevention; Post partum haemorrhage; Mother to child transmission of HIV; Misoprostol